Orientation independent heat transport characteristics of diamond/copper interface with ion beam bombardment. (November 2021) - Yang, Kunming; Zhang, Zhongyin; Zhao, Haohao; Yang, Bihuan; Zhong, Boan; Chen, Naiqi; Song, Jian; Chen, Chu; Tang, Dawei; Zhu, Jie; Liu, Yue; Fan, Tongxiang
Abstract: Owing to high thermal conductivity ( k ) and appropriate coefficient of thermal expansion (CTE), Diamond/copper (Dia/Cu) composites have attracted extensive attention as advanced thermal management materials, but also suffered with low thermal boundary conductance ( G ). This is because complex energy carrier behaviors at metal/nonmetal interfaces. Although conventional carbide forming interlayers may serve as acoustic matching bridge, crystallographic orientation is still critical to influence heat transport characteristics of Dia/Cu interface. In this work, both theoretical calculations and time-domain thermoreflectance (TDTR) results revealed two distinct G of (100) and (111) Dia/Cu interfaces. We then applied an easy-controlled ion-beam bombardment technique to reduce the orientation dependent G, and two different trends are observed with ion-bombardment time ( t ): (1) when t < 30 min, G increases with increasing t ; (2) when t > 30 min, G decreases with increasing t . Our microstructural and surface potential analysis suggests sp 3 -to-sp 2 hybridization and formation of nanoscale amorphous carbon (a–C) layer at the diamond surface. The coupling between electrons in Cu and a–C provides an additional heat transport pathway, however, the interfacial defect scattering becomes dominant when continuously increasing ion-bombardment time. The present findings may provide more insight to understand the orientation dependent heat transport mechanisms at metal/nonmetal interfaces. Graphical abstract: Image, graphical abstract